A, The Policy For Promoting The Existence Of Exoticism In Surabaya As A Spice Route Point - Putri, Nabila Ananda; Rohmadani, Eka Suci; Putri, Ananda Islami Aulia; Maulita, Nirma; Ariawantara, Putu Aditya Ferdian (Journal of Education on Social Science (JESS), 2025)
The spice commodity trade has shaped the history of sea trade routes, which cannot be separated from Surabaya's important role in international relations. The Indonesian government has made the spice route a cultural priority for 2021 to gain world cultural heritage recognition. This research uses a mixed method with three approaches: phenomenological, cross-sectional, and quasi-experiment. The results of this research include: (a) Public understanding regarding the existence of the exoticism of the Surabaya spice route is still low; (b) Low knowledge regarding evidence of the spice route in Surabaya; and (c) There is a need for media that can promote the existence of the exoticism of the spice route. Based on these results, researchers offer promotional media in the form of the Arempaja board game to communicate the exotic existence of the Surabaya spice route to the broader community, especially the younger generation. In line with this solution, researchers utilized the connectionist theory by Edward L Thorndike, relating stimulus events (s) to responses (r). The contents of the Arempaja board game are taken from the results of in-depth interviews with several perspectives and direct visits to trail points on the Surabaya spice route. Based on the results of the effectiveness test, it was found that the Arempaja board game increased players' understanding of the Surabaya spice route. This research concludes that the Arempaja board game is suitable for promotional media or learning media regarding the exotic existence of the Surabaya spice route.